2022
DOI: 10.1177/10541373221088391
|View full text |Cite
|
Sign up to set email alerts
|

Coping Orientation of Academic Community in the Time of COVID-19 Pandemic: A Pilot Multi-Country Survey Study

Abstract: In this paper, we have mapped the coping methods used to address the coronavirus pandemic by members of the academic community. We conducted an anonymous survey of a convenient sample of 674 faculty/staff members and students from September to December 2020. A modified version of the RCOPE scale was used for data collection. The results indicate that both religious and existential coping methods were used by respondents. The study also indicates that even though 71% of informants believed in God or another rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Some studies conducted research on psychological resilience during the COVID-19 pandemic [ 12 , 13 ]. During the first wave of COVID-19, a U.S. study showed that psychological resilience was significantly lower when compared to earlier normative data, as measured by the CD-RISC scale [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies conducted research on psychological resilience during the COVID-19 pandemic [ 12 , 13 ]. During the first wave of COVID-19, a U.S. study showed that psychological resilience was significantly lower when compared to earlier normative data, as measured by the CD-RISC scale [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…University faculty/staff and students were among the groups affected by working from home. Working from home changed the working environment for many employees, presenting both challenges and opportunities for work life [2]. People in academic settings faced a new reality with the closure of campus-based in person activities, and the shift of teaching to different online platforms [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, meaning-making coping has had an important place in academics' effort to cope with COVID-19. Using nature as a coping resource and considering life as integrated to a greater whole are significant for coping with COVID-19 among the academics, and in other traumatic situations [2,21]. Additionally, religious coping methods have been used, especially in the context of Muslim academics [22,23].…”
Section: Introductionmentioning
confidence: 99%